PELAKSANAAN HUKUMAN MATI DALAM PERSEPEKTIF HAK ASASI MANUSIA - Heriyono Heriyono (Indonesian Journal of Law and Policy Studies, 2020)
In 2015 the Government of Indonesia carried out three stages of executions of 18 inmates, out of 18 convicted prisoners, only 4 inmates were Indonesian citizens, the rest were foreign nationals, this was what later made the execution of death executions by the Indonesian government in 2015 a global spotlight . For the Indonesian government, the execution of several people convicted of narcotics and illegal drugs is a logical consequence of the spirit of law enforcement in Indonesia. It is also evidence of the government's commitment in its fight against drugs. In Indonesia, violations and crimes against the misuse of narcotics and illegal drugs are high class crimes (extra ordinary crime) as well as terrorism. This article discusses how the history of the death penalty, then also about the existence of the implementation of the death penalty in the legal system in Indonesia, furthermore also about the debate and pros and cons of the implementation of the death penalty, and the last is about the implementation of the death penalty in the perspective of human rights relativeiseme. This arithmetic draws the conclusion that the development of the pendang way of carrying out the death penalty is strongly influenced by historical factors of the country concerned. In addition, natural factors (culture) and culture (culture) also influence the development of thought implementation and application of the death penalty.